Ժողովրդավարության մակարդակի ինդեքսը. Հայաստանի, Վրաստանի, Ադրբեջանի, Ռուսաստանի, Բելառուսի, Ղազախստանի, Ուկրաինայի և Մոլդովայի համեմատական միջերկրային վերլուծություն (2012թ) - Արուսյակ Ալեքսանյան (ՀՀ ԳԱԱ հրատ.)
В статье автор представляет модель оценки уровня демократии (Индекс уровня демократии), основанную на методе построения индексов. Используя модель, автор так же исследует Индекс уровня демократии Армении, Грузии, Азербайджана, России, Беларуси, Казахстана, Украины и Молдовы 2012 года и дает сравнительный анализ.In the article, the model for determining the level of democracy (Index of Democracy Level) is presented based on the method of index construction. Using the model, the author also examines and presents the Index of Democracy Level of Armenia, Georgia, Azerbaijan, Russia, Belarus, Kazakhstan, Ukraine and Moldova in 2012 and makes comparative analysis.
Keywords: Political Science